2009
DOI: 10.5194/acp-9-9299-2009
|View full text |Cite
|
Sign up to set email alerts
|

Composition and properties of atmospheric particles in the eastern Atlantic and impacts on gas phase uptake rates

Abstract: Abstract. Marine aerosol composition continues to represent a large source of uncertainty in the study of climate and atmospheric chemistry. In addition to their physical size and chemical composition, hygroscopicity plays a significant role, increasing the particles' surface areas and scattering potential. Simultaneous aerosol measurements were performed on board the RRS Discovery and at the Cape Verde atmospheric observatory during the Aerosol Composition and Modelling in the Marine Environment (ACMME) and R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 81 publications
11
63
0
Order By: Relevance
“…This disagreement is likely due to the different approach used to derive clean marine OM values for ICEALOT (i.e., Positive Matrix Factorization). Our mean OM value (0.77 µg m −3 , see Table 1) is higher than the number obtained by Allan et al (2009) during RHaBMLe for their "clean" 40-h period (0.29 µg m −3 ), identified based on the back trajectories analysis. Their criteria were more conservative and they excluded time periods with measurements exhibiting high variability in composition and air mass history.…”
Section: Measurements Of Aerosol Compositionmentioning
confidence: 67%
“…This disagreement is likely due to the different approach used to derive clean marine OM values for ICEALOT (i.e., Positive Matrix Factorization). Our mean OM value (0.77 µg m −3 , see Table 1) is higher than the number obtained by Allan et al (2009) during RHaBMLe for their "clean" 40-h period (0.29 µg m −3 ), identified based on the back trajectories analysis. Their criteria were more conservative and they excluded time periods with measurements exhibiting high variability in composition and air mass history.…”
Section: Measurements Of Aerosol Compositionmentioning
confidence: 67%
“…However, the lack of a high growth factor mode in the HTDMA-CPC (e.g. Allan et al, 2009) would suggest that sea salt is not an important contributor to the number concentrations at the dry sizes under investigation here. As the AMS does not measure sea salt, it is difficult to critically assess whether including this improves closure.…”
Section: Growth Factor Modellingmentioning
confidence: 99%
“…Elemental carbon (EC) during the subtropical events in the Miyazaki et al (2010) study averaged 43 ng m −3 . Less directly, hygroscopic growth experiments in the Southern Atlantic and Indian Oceans (Maßling, 2003), the Pacific and Southern Oceans (Berg et al, 1998), near Puerto Rico (Allan et al, 2008) and the Eastern Atlantic (Allan et al, 2009) all found hygroscopic growth of aerosol particles consistent with particles composed chiefly of sulfate salts rather than OM during clean marine periods.…”
Section: M Shank Et Al: Organic Matter and Non-refractory Aerosolmentioning
confidence: 99%